Left Ventricular Outflow Tract Pseudoaneurysm Formation Following Three Aortic Valve Replacement Surgeries - Ibrahim, Nasrien E. (Heart Views, 2015)
We present a case of a pseudoaneurysm arising from the left ventricular outflow tract/aortic root as a complication of aortic valve surgery. A 45-year-old Nigerian female presented to our institution's emergency department with chest discomfort. She had three bioprosthetic aortic valve replacements in the preceding year at an outside institution for aortic regurgitation and wanted a second opinion on remaining surgical options. The learning points relevant to this case are as follows: (1) Recognizing potential complications postmultiple valve surgeries, (2) screening patients for chronic infections and rheumatologic conditions that can contribute to failed valve surgeries.